2022
DOI: 10.1021/acsmedchemlett.2c00300
|View full text |Cite
|
Sign up to set email alerts
|

Development of an N-Terminal BRD4 Bromodomain-Targeted Degrader

Abstract: Targeted protein degradation is a powerful induced-proximity tool to control cellular protein concentrations using small molecules. However, the design of selective degraders remains empirical. Among bromodomain and extra-terminal (BET) family proteins, BRD4 is the primary therapeutic target over family members BRD2/3/T. Existing strategies for selective BRD4 degradation use pan-BET inhibitors optimized for BRD4:E3 ubiquitin ligase (E3) ternary complex formation, but these result in residual inhibition of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The resulting residue was purified by column chromatography (CombiFlash Rf system: 24 g of silica, hexanes/ethyl acetate, 0−100% ethyl acetate, 16 min) (Scheme 4). (21). Following the general procedure C, sulfone 17 was alkylated with bromide 19, sulfone 17 29 (280 mg, 0.822 mmol, 1.0 eq), bromide 19 43 (258 mg, 1.03 mmol, 1.5 eq), K 2 CO 3 (227 mg, 1.64 mmol, 1.5 eq), and DMF (8.0 mL).…”
Section: N-(2-(2-(2-(7-((5-chloro-1-methyl-6-oxo-16-dihydropyridazin-...mentioning
confidence: 99%
“…The resulting residue was purified by column chromatography (CombiFlash Rf system: 24 g of silica, hexanes/ethyl acetate, 0−100% ethyl acetate, 16 min) (Scheme 4). (21). Following the general procedure C, sulfone 17 was alkylated with bromide 19, sulfone 17 29 (280 mg, 0.822 mmol, 1.0 eq), bromide 19 43 (258 mg, 1.03 mmol, 1.5 eq), K 2 CO 3 (227 mg, 1.64 mmol, 1.5 eq), and DMF (8.0 mL).…”
Section: N-(2-(2-(2-(7-((5-chloro-1-methyl-6-oxo-16-dihydropyridazin-...mentioning
confidence: 99%
“…In the last few years, selective BD1 or BD2 inhibitors were discovered and have enabled elucidation of the differential roles played by these two domains in gene transcription and human diseases. In addition, BRD4 inhibitors with >10-fold binding selectivity over BRD2 and BRD3 have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the development of bromodomain inhibitors, the major advancement in induced target protein degradation using the PROTAC technology has enabled the discovery of highly potent degraders of the BET proteins. , While most of the reported BET degraders induce degradation of BRD2, BRD3, and BRD4 with similar potencies, compounds displaying selective degradation of BRD4 over BRD2 and BRD3 have been reported. ,, MZ1, reported by Ciulli et al, was the first selective BRD4 degrader and was designed using JQ1, a pan BET inhibitor, and a VHL-1 ligand. A subsequent study showed that MZ1 induced de novo contacts between BRD4 protein and VHL-1, forming a stable ternary complex and causing the selective degradation of BRD4 over that of BRD2 or BRD3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations